Pengaruh Reputasi Merek dan Ulasan Online terhadap Keputusan Pembelian Online Melalui Kepercayaan Pelanggan (Studi pada Konsumen Skincare Lulur Produk Sariayu) - Halimatus Sa'diyah; Nindria Untarini (J-MAS (Jurnal Manajemen dan Sains), 2026)
The hyper-competitive local skincare industry has caused the market position of heritage brands like Sariayu to fluctuate, even leading to a decline in the brand strength index (TBI) of up to 3.1% in the body scrub category by 2025. This situation indicates a challenge for legendary brands to remain relevant amidst the dominance of Gen Z and Millennial consumers who rely heavily on digital information. This study aims to examine and analyze the influence of brand reputation and online reviews on online purchasing decisions by positioning customer trust as a mediating variable. The approach used is a quantitative survey with an explanatory research design. Data were collected through online questionnaires distributed to Sariayu body scrub consumers throughout Indonesia using a purposive sampling technique. A total of 230 valid respondents served as the main sample in this study. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software to test the causal relationship and mediating role between variables. The results of the study are expected to provide a comprehensive picture of the extent to which legacy reputation and digital reviews are able to build trust that then converts intention to actual purchasing decisions. These findings are intended to provide a strategic foundation for traditional cosmetic brands in adapting digital marketing and managing electronic word of mouth (e-WOM) to maintain loyalty and competitiveness in the modern marketplace.